2017
DOI: 10.2147/dddt.s145716
|View full text |Cite
|
Sign up to set email alerts
|

Metal organic frameworks as a drug delivery system for flurbiprofen

Abstract: BackgroundMetal organic frameworks (MOFs) have attracted more attention in the last decade because of a suitable pore size, large surface area, and high pore volume. Developing biocompatible MOFs such as the MIL family as a drug delivery system is possible.PurposeFlurbiprofen (FBP), a nonsteroidal anti-inflammatory agent, is practically insoluble in aqueous solution, and, therefore, needs suitable drug delivery systems. Different biocompatible MOFs such as Ca-MOF and Fe-MILs (53, 100, and 101) were synthesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(72 citation statements)
references
References 33 publications
1
69
1
1
Order By: Relevance
“…Release behaviors of MTX and CUR adsorbed on the surface of the synthesized MOFs were investigated in PBS (pH = 7.4) solution at 37 °C under continuous stirring for 72 hr. As shown in Figure , the MTX and CUR release profiles exhibited two stages, which this behavior is related to the location of drugs within the pores of MOF nanoparticles, dimension of pore sizes, and the kind of interactions between drug molecules and MOF nanoparticles . The first rapid release which took place during 10 hr indicated that a significant amount of drug molecules is adsorbed on the surface of MOF nanoparticles and release easily because of simple diffusion and dissolution of drug molecules in release medium and it is independent of drug concentrations .…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Release behaviors of MTX and CUR adsorbed on the surface of the synthesized MOFs were investigated in PBS (pH = 7.4) solution at 37 °C under continuous stirring for 72 hr. As shown in Figure , the MTX and CUR release profiles exhibited two stages, which this behavior is related to the location of drugs within the pores of MOF nanoparticles, dimension of pore sizes, and the kind of interactions between drug molecules and MOF nanoparticles . The first rapid release which took place during 10 hr indicated that a significant amount of drug molecules is adsorbed on the surface of MOF nanoparticles and release easily because of simple diffusion and dissolution of drug molecules in release medium and it is independent of drug concentrations .…”
Section: Resultsmentioning
confidence: 94%
“…The second step of release could be defined as a slow and steady process, which took as long as 60 hr, because of the normal desorption of drug molecules from the pores of MOFs, diffusion and consequently dissolution in release medium. This observation might be attributed to the different host‐guest interactions between the adsorbents and the adsorbate molecules, including hydrogen bonds and л‐л interaction of the organic ligands of the adsorbent frameworks with the aromatic structure of MTX and CUR drugs (see Figure S4) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The last decade, in an effort to exploit the inherent properties of MOFs, such as porosity, modular surface chemistry, large surface areas, and tunable pore sizes, various research groups explored the potential uses of MOF-based materials as drug delivery systems [85,86]. The low chemical and aqueous stability of some MOF structures render them highly promising candidates for drug delivery applications, taking into consideration that MOF structural units need to be biodegraded after the drug release.…”
Section: Drug Delivery Systems (Dds)mentioning
confidence: 99%